An Overview of Enterprising Theory - Sharma, Devilal (Journal of Nepalese Business Studies, 2009)
National priority of the developing country for rapid economic development and reducing growing unemployment problems may be encouraging entrepreneurship developments and entrepreneurial characteristics to the younger people. Either through University education or through different government’s policy it should be ensured that the investment friendly environment as well as youth’s energy should be divert in entrepreneurial way to creating opportunity for self-economical development of the people. Scholars as well as academician’s attention also should be concentrates on the matter. Thus the article focuses to fill that gap of national priority of developing nation like Nepal. Key Words: Entrepreneurship, enterprise, opportunity, uncertainty, governance, judgments, decision-making, management, transaction cost theory, value. The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page:112-119